If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = x + 3 + -1x Reorder the terms: 3 = 3 + x + -1x Combine like terms: x + -1x = 0 3 = 3 + 0 3 = 3 Add '-3' to each side of the equation. 3 + -3 = 3 + -3 Combine like terms: 3 + -3 = 0 0 = 3 + -3 Combine like terms: 3 + -3 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5-(8-c)=0 | | 7x=109.2 | | y=12x+420 | | 260=k(1300) | | 2x=12.25 | | 48=k(6) | | 8m-(6m-3)=9 | | 3n-(5n+2)=8 | | 12h-18=12h-18 | | 6(y+2)-2y=15 | | 2x+19=1x-80 | | 6-(3x-3)-[2(-4x-1)]=(-3x+2) | | 12-2x=7x-15 | | 5n-9=2n+3 | | -(-4x+6-8)= | | -f(x-2)g=(x^2-3+2) | | 18=k(3) | | -24x+4x^2=0 | | (3x+72)(x-1)= | | 5x=x+26 | | 12h-18=(4h-6) | | 12x-60=0 | | 6(4y-1)=5 | | 2(x+5)=8 | | 3-n=33 | | x-6=(x-4)1/2 | | y=1.5(1) | | V=dt | | 4x^2-8=20 | | 0=1.5x | | 10(-10x+1)= | | 9n^2-50n-80=0 |